PERSONALITY TRAITS, ENVIRONMENTAL CONDITIONS, AND SOCIOECONOMIC STATUS AS PREDICTORS OF MENTAL HEALTH OUTCOMES AMONG COUPLES IN IBADAN METROPOLIS, NIGERIA - Afolabi, Abimbola (African Journal of Social and Behavioural Sciences, 2026)
Mental health is a fundamental component of overall well-being, intricately linked to the quality of life and interpersonal relationships, particularly among married couples. The significance of mental health transcends individual experiences, as it affects the dynamics of relationships, communication patterns, and emotional support systems within couples. This study examined personality traits, environment and socioeconomic status as predictors of mental health among couples in Ibadan metropolis. The research design is descriptive. Quantitative method of data collection was adopted. A sample of 215 participants was selected using a simple random sampling. A questionnaire focusing on demographic variables, personality traits, environmental stress, socioeconomic status and mental health was administered to the participants. Data were analysed using descriptive statistics, Pearson product-moment correlation and regression analysis at a 0.05 level of significance. Three hypotheses were tested. The findings of hypothesis one indicated that there was a statistically significant positive correlation between personality traits and mental health, r = 0.34, p = 0.000. Test of hypothesis two indicated there was a statistically significant positive correlation between environmental factors and mental health, r = .32, p < .001. Test of hypothesis three indicated that the combination of personality traits, environmental factors, and socioeconomic status significantly predicts mental health outcomes (F(3, 211) = 140.26, p < .001, with R² = 0.67). The practical implication of this finding is that the favourable environmental factors and socio-economic factors are associated with improved mental health outcomes among married couples when compared to their counterparts. The study recommended that couples should engage in open and honest communication to address challenges related to personality differences, environmental stressors, and socioeconomic pressures, as this will foster emotional closeness and improve mental health outcomes. Couples should work together to build a nurturing and stable home environment free from conflict and excessive stress, as a positive environment has been shown to significantly improve the mental wellbeing of married partners. Couples facing persistent challenges related to personality clashes or environmental and financial pressures should seek professional help through marital counseling or therapy to gain coping strategies and strengthen their relationship. Finally, since socioeconomic status influences mental health, couples should engage in joint financial planning, budgeting, and goal-setting to reduce stress caused by economic instability and improve their overall quality of life.